Evaluation of User Interface (UI) and User Experience (UX) in A Web-Based Entrepreneurial Student Application - Ellya Kurniawan, Jimmy; Rahmawati, Kuncoro Dewi; Larasati Rembulan, Cicilia; Tanuwijaya, Evan (Universitas Ciputra Surabaya, 2026)
Measurement of entrepreneurial orientation remains limited and is predominantly conducted using manual methods. To address this gap, this study aims to develop a web-based application for measuring entrepreneurial orientation—which has not previously been developed—and to examine its reliability, user interface (UI), and user experience (UX). The instrument used is an adaptation of the entrepreneurial orientation scale, which was converted into a website-based format and complemented with recommendation features and user constraint identification. Data were collected through a focus group discussion (FGD) involving junior and senior high school teachers and students (N = 5), as well as a survey of junior and senior high school students (N = 60) following a trial of the web-based